2020
DOI: 10.1194/jlr.ra120001066
|View full text |Cite
|
Sign up to set email alerts
|

β-Carotene conversion to vitamin A delays atherosclerosis progression by decreasing hepatic lipid secretion in mice

Abstract: Atherosclerosis is characterized by the pathological accumulation of cholesterol-laden macrophages in the arterial wall. Atherosclerosis is also the main underlying cause of cardiovascular diseases (CVDs), and its development is largely driven by elevated plasma cholesterol. Strong epidemiological data find an inverse association between plasma β-carotene with atherosclerosis, and we recently showed that β-carotene oxygenase 1 (BCO1) activity, responsible for β-carotene cleavage to vitamin A, is associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 68 publications
5
48
0
Order By: Relevance
“…These data are consistent with a recent study showing that retinoic acid reduced hepatic lipoprotein secretion. [ 25 ] These data also confirm an alteration of lipid metabolism in rats as a symptom of vitamin A deficiency, in agreement with previous published data. [ 26,27 ] In particular, Oliveros and colleagues showed that vitamin A deficiency induced a hypolipidemic effect by decreasing both serum triglyceride and cholesterol levels in male rats.…”
Section: Discussionsupporting
confidence: 92%
“…These data are consistent with a recent study showing that retinoic acid reduced hepatic lipoprotein secretion. [ 25 ] These data also confirm an alteration of lipid metabolism in rats as a symptom of vitamin A deficiency, in agreement with previous published data. [ 26,27 ] In particular, Oliveros and colleagues showed that vitamin A deficiency induced a hypolipidemic effect by decreasing both serum triglyceride and cholesterol levels in male rats.…”
Section: Discussionsupporting
confidence: 92%
“…Dietary carotenoids, including BC and subcutaneously administered retinoids such as retinoic acid, ameliorate obesity and obesity development in animal models, and there is evidence of the same sense in humans [ 3 , 4 , 5 , 6 , 7 ]. Additionally, the beneficial effects of BC administration on blood glucose levels [ 8 ] and BC conversion into vitamin A on blood lipids and atherosclerosis progression [ 9 , 10 ] were described in pre-clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, performed in the same animal model that consumption of a natural β-carotene enriched foods, composed of all-trans and 9-cis isomers, inhibited atherogenesis compared to the vitamin A deficiency diet, while vitamin A did not 39 . Recently, it has been shown that β-carotene and retinoic acid administration reduces the development of atherosclerosis, presumably by a reduction of the secretion of newly synthesized triglyceride and cholesteryl ester 40 . It has also been shown that 9-cis-RA stimulated macrophage cholesterol efflux and inhibited atherosclerotic plaque formation in Apo-E mice 41 .…”
Section: Discussionmentioning
confidence: 99%